Assessing the Impact of District Primary Education Program in India. Issue 4 (14th August 2016) - Azam, Mehtabul; Saing, Chan Hang
Abstract: We examine the impact of India's District Primary Education Program (DPEP) introduced in the mid‐1990s. We exploit the fact that the DPEP was targeted towards primary school age children and was introduced in phases to different districts in India, and many of the districts never got the program to implement a difference‐in‐difference strategy to find the causal impact of the program on probability of attended primary school, probability of completed primary education and years of schooling. We find that the DPEP program increased the probability of attended primary school and completed primary school by about 2 percentage points. Similarly, the program increased the years of schooling by 0.16 years.